Concerns and Challenges of Data Integration from Objective Post-Positivist Approach and a Subjective Non-Positivist Interpretive Approach and Their Validity/Credibility Issues - Khanal, Ram Chandra (Journal of the Institute of Engineering, 2014)
Integration of data derived from objective post positivist approach and interpretive non-positivist approach through mixed methods research has gained increasing attention in the recent past. But, at the same, concerns have been raised in the process of integrating data and, hence, enhancing validity/credibility of a research. This article seeks to analyze some concerns and challenges related to these aspects and provides some process to address these challenges. This article reviewed various peer reviewed journals and other grey literatures focusing on data integration within mixed method research. The paper presents some theoretical and methodological concerns and challenges of data integration and reviews two validity/credibility frameworks. Based on these review, the paper outlines a strategy of data integration. The strategy includes selection of appropriate research methodology and data conversion processes based on the research need. The paper provides a four step process for data conversion by adopting quantitizing approach which include; creating focus questions, response coding, thematic categorizing and employing qualitative data analysis process. DOI: http://dx.doi.org/10.3126/jie.v9i1.10677 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 115–129